2016
DOI: 10.1186/s12940-016-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to mining industry and respiratory diseases in children in a community in Northern Chile: A cross-sectional study

Abstract: BackgroundIn a community in northern Chile, explosive procedures are used by two local industrial mines (gold, copper). We hypothesized that the prevalence of asthma and rhinoconjunctivitis in the community may be associated with air pollution emissions generated by the mines.MethodsA cross-sectional study of 288 children (aged 6–15 years) was conducted in a community in northern Chile using a validated questionnaire in 2009. The proximity between each child’s place of residence and the mines was assessed as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…According to the spatial Bayesian model, closer the residents to the mines more the chances of getting the disease and if it is less than 1.8 KM, the chances of getting the respiratory disease is negligible. These findings of respiratory diseases among coal mine workers are identical to the one found out, and such association in industrial gold or copper mines due to air pollution nearby observed in rural areas of China (Herrera et al, 2016).…”
Section: Chronic Lower Respiratory Diseasesupporting
confidence: 88%
“…According to the spatial Bayesian model, closer the residents to the mines more the chances of getting the disease and if it is less than 1.8 KM, the chances of getting the respiratory disease is negligible. These findings of respiratory diseases among coal mine workers are identical to the one found out, and such association in industrial gold or copper mines due to air pollution nearby observed in rural areas of China (Herrera et al, 2016).…”
Section: Chronic Lower Respiratory Diseasesupporting
confidence: 88%
“…Data for the analyses were obtained from a questionnaire-based cross-sectional study [ 14 , 19 ]. In brief, the study included 288 children attending 1st–6th grade at two larger elementary schools in the community (417 were invited to participate, response: ).…”
Section: Methodsmentioning
confidence: 99%
“…Using the global positioning system (GPS), we established the latitude and longitude coordinates of children’s residences and the primary locations of the mining extraction procedures ( Figure 1 ). Based on this, we calculated residential proximity to the gold and copper mine [ 14 ]. We considered the first and the second distance quartile to each mine and to either mine [ 12 ] as exposed categories and compared them to those living at least within the median distance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations